A PROSPECTIVE STUDY TO ANALYSE THE SIDE EFFECTS OF OLMESARTAN MEDOXOMIL AND ENALAPRIL IN HYPERTENSIVE SUBJECTS - Singh, Parminderpal; Kiranjit, Kiranjit (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The present study was aimed to analyze the side effects of olmesartan medoxomil and enalapril in hypertensive subjects. Methods: The study consisted of newly diagnosed hypertension categorized according to 7th report of Joint National Commission on prevention, detection, evaluation, and treatment of high blood pressure. The subjects were divided into two groups. The Group A subjects received olmesartan, and Group B subjects received enalapril. Pressure was recorded both in supine and sitting positions. The appearance of side effects was observed in the follow-up, i.e., dry cough, headache, postural hypotension, angioedema, dizziness, skin rashes, taste alterations, and urticaria. A statistical data were prepared on the basis of information obtained and analyzed thoroughly for antihypertensive effects and side effects of olmesartan and enalapril. SPSS software was used for analysis. Results: There was observed an increase in the incidence of taste alteration with drug therapy in Group B (Enalapril). There was observed an increase in the incidence of postural hypotension with drug therapy in both groups. In Group A (Olmesartan), the incidence of postural hypotension at the beginning of trial, 4 weeks, and 8 weeks was 0%, 2%, and 2%, respectively. In Group A (Olmesartan), there was no incidence of a headache at the beginning of trial, at 4 weeks and 8 weeks. Conclusion: From the study, it can be concluded that both olmesartan and enalapril are effective in Stage I and Stage II hypertension, but olmesartan is tolerated well with lesser side effects.